Object and intention under Article 101 TFEU: Lessons from Australia, New Zealand and analytical jurisprudence. (September 2019) - Kwok, Kelvin Hiu Fai
What does it mean for an agreement to have an anticompetitive 'object' under Article 101(1) of the Treaty on the Functioning of the European Union? Can the European Commission support an 'object' case by reference to the agreement parties' subjective intention, and if so, how? What exactly is the relationship between an agreement's object and the parties' subjective intention under competition law? This article is the first to bring insights from Australian and New Zealand cases, as well as analytical jurisprudence, to bear on these underexplored yet important questions affecting the European Union and common law jurisdictions around the world. Using Ronald Dworkin's theory of legal interpretation as the analytical basis, this article argues for a 'mixed' conception of the 'object' concept which enables an anticompetitive object to be proven either objectively or subjectively. Anticompetitive subjective intention accordingly provides an independent, alternative basis for competition law liability for agreements; the lack of such intention, meanwhile, does not help exculpate parties who are liable based on their objective purpose to restrict competition. This article also argues that voluntariness and evidentiary limits ought to be imposed on the use of anticompetitive subjective intention in the 'object' analysis of agreements.